The influence of emotional intelligence and creativity on work performance and commitment - Kiran Kumar Thoti; Roselina Ahmad Saufi (2014)
The employment customs is stirring drastically on an ordinary basis as the organization and employees’. In increasing of technological transform, competition and globalization continues perhaps with increasing employees’ work commitment and work performance. According to Turner, Barling and Zacharatos (2002), at present employees have to be allied to their work physically, emotionally and mentally in order to deliver stupendous performance. Lately many of organizations suffer because of low employee morality and productivity. As a result, operational costs increase and the quality of the outcome also affected. Poor emotional intelligence may slow down the employees’ performance. As a result employees are not motivated to work hard, besides that they do not have the ability to manage their emotions. Managers who supposing to monitors and manages the staff in most organizations are very slow in giving feedbacks and stimulate employees. Addition to, they were also facing difficulty in designation of works in order to enhance their employees’ work commitment and improve their performance. Employee can develop his or her emotional intelligence skills throughout their life. Employee and manager can improve their own emotional intelligence skills by learning the accurate methods to reduce stress. On the other hand, creativity can expand their capability to think, to produce new ideas, to make changes in organization which can influence their attitude to work hard and to increase their commitment through organization. The creativity of employees is very important to improve organizations if organizations are competing to achievement in today’s globally aggressive milieu. Creative manager and employee can assist their companies to overcome rigid and traditional problem solving approaches. This study seeks to examine the relationship between emotional intelligence and creativity on employees’ work commitment and work performance. This paper will contribute to the body of knowledge by filling the gap of the literature and will appear as a reference for those who help in the initiating process.